Factors That Influence the Service Recovery Performance (A Study in Bauchi Specialist Hospital in Nigeria) - Aminu, Adamu Faggo (2012)
Many public sector hospitals are often blamed and criticized for their lack of speed and low level of service quality. Rod & Ashill (2010) write that numerous studies have concluded that patients perceive public to be inferior in the quality of their service provision. Yet public are the only option for the most people. One reason is because they have the best facilities. Public healthcare providers can fall short of a patient’s expectation at any point (Fotler et al, 2009) or make mistake. When healthcare provider take proactive steps to manage, the customers feeling, especially when there is a gap between the customers expectation and what they actually experience, such action are referred to as service recovery performance. Service Recovery is more than just fixing the problem. Service recovery performance is all about doing things right the second time. Thus the objective of this research is to get the better understanding of the factors that influence service recovery performance ie to improve the service delivered by the public hospital in Nigeria to know which factors to give priority on the influencing of service recovery performance which in return will revive the image of public hospital in Nigeria. Hence in this research the factors influencing service recovery performance in Bauchi state Specialist hospital, Nigeria is measured, using questionnaires items adapted from Ashill, et al (2005). A self-administered questionnaire was used to assess customer service training, empowerment and teamwork. The respondent involved in this research are public hospital staffs (clinical and non-clinical) in Bauchi state, Nigeria. To collect data for the study, 225 questionnaires were distributed in the hospital. 190 questionnaires were retrieved.